PENGARUH HARGA, KUALITAS PELAYANAN DAN LOKASI TERHADAP LOYALITAS PELANGGAN PADA SUGAR CAFÉ BATAM - Rudi Hartono; Tiurniari Purba (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
This study aims to analyze and to explain the effect of price, service quality and location on customer loyalty at Sugar Café Batam. The population in this study amounted to 250, while the sample used in this study was 150. The data collection technique used in this study was non-profitability sampling, and data testing in this study used the SPSS 21 program. The results of this study state that Price affects customer loyalty, service quality affects customer loyalty, and location affects customer loyalty.